Steroids Provide Temporary Improvement of Refractory Pain Following Subarachnoid Hemorrhage. (July 2023) - Jaffa, Matthew N.; Podell, Jamie E.; Foroutan, Arshom; Motta, Melissa; Chang, Wan-Tsu W.; Cherian, Jacob; Pergakis, Melissa B.; Parikh, Gunjan Y.; Simard, J. Marc; Armahizer, Michael J.; Badjatia, Neeraj; Morris, Nicholas A.
Introduction: Evidence for optimal analgesia following subarachnoid hemorrhage (SAH) is limited. Steroid therapy for pain refractory to standard regimens is common despite lack of evidence for its efficacy. We sought to determine if steroids reduced pain or utilization of other analgesics when given for refractory headache following SAH. Methods: We performed a retrospective within-subjects cohort study of SAH patients who received steroids for refractory headache. We compared daily pain scores, total daily opioid, and acetaminophen doses before, during, and after steroids. Repeated measures were analyzed with a multivariable general linear model and generalized estimating equations. Results: Included 52 patients treated with dexamethasone following SAH, of whom 11 received a second course, increasing total to 63 treatment epochs. Mean pain score on the first day of therapy was 7.92 (standard error of the mean [SEM] .37) and decreased to 6.68 (SEM .36) on the second day before quickly returning to baseline levels, 7.36 (SEM .33), following completion of treatment. Total daily analgesics mirrored this trend. Mean total opioid and acetaminophen doses on days one and two and two days after treatment were 47.83mg (SEM 6.22) and 1848mg (SEM 170.66), 34.24mg (SEM 5.12) and 1809mg (SEM 150.28), and 46.38mg (SEM 11.64) and 1833mg (SEM 174.23), respectively. Response to therapy was associated with older age, decreasing acetaminophen dosing, and longer duration of steroids. Hyperglycemia and sleep disturbance/delirium effected 28.6% and 55.6% of cases, respectively. Conclusion: Steroid therapy for refractory pain in SAH patients may have modest, transient effects in select patients.